Hadith #2135 - Sunan Abi Dawud - Aabad bin 'Aabad bin Habib عباد بن عباد بن حبيب بن المهلب; Aisha bint Abi Bakr; Asim al-Ahwal عاصم الأحول; Mu'adhah bint 'Abdullah معاذة بنت عبد الله; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
On the authority of his father that ‘Aishah said: O my nephew, the Messenger of Allah (ﷺ) did not prefer one of us to the other in respect of his division of the time of his staying with us. It was very rare that he did not visit us any day (i.e. he visited all of us every day). He would come near each of his wives without having intercourse with her until he reached the one who had her day and passed his night with her. When Saudah daughter of Zam’ah became old and feared that the Messeng
Grade: Hasan Sahih

Hadith #2242 - Sunan Abi Dawud - al-Dhak bin Fyrwz al-Dylmy الضحاك بن فيروز الديلمي; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Wahb bin Jarir bin Hazim bin Zayd وهب بن جرير بن حازم بن زيد; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي; Yahya bin Ma'in يحيى بن معين; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Qais bin Al Harith through a different chain of narrators to the same effect.
Grade: Sahih

Hadith #2491 - Sunan Abi Dawud - Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Hisham bin Yusuf al-Sana'i هشام بن يوسف الصنعاني أبو عبد الرحمن; Ma'mar bin Rashid معمر بن راشد; Yahya bin Ma'in يحيى بن معين; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
Anas bin Malik said “Whenever the Apostle of Allaah(ﷺ) went to Quba, he used to visit Umm Haram daughter of Milhan who was married to ‘Ubadah bin Al Samit. One day when he visited her she gave him food an sat clearing his head of lice. The narrator narrated the rest of the tradition. Abu Dawud said “Daughter of Milhan died in Cyprus”.
Grade: Sahih

Hadith #2544 - Sunan Abi Dawud - Abu Ahmed al-Mu'dab الحسين بن محمد بن بهرام - أبو علي المؤدب; ibn Abbas; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
The Prophet (ﷺ) said: Keep to every sorrel horse with a white blaze and white on the legs, or dark bay with a white blaze. He then mentioned something similar. Muhammad ibn al-Muhajir said: I asked him: Why was a sorrel horse preferred? He replied: Because the Prophet (ﷺ) had sent a contingent, and the man who first brought the news of victory was the rider of a sorrel horse.
Grade: Da'if

Hadith #2626 - Sunan Abi Dawud - Abdul Samad bin 'Abdul Warith bin Sa'id عبد الصمد بن عبد الوارث بن سعيد; Hameed bin Hilal حميد بن هلال; Sulaiman bin al-Mughira al-Qaysy سليمان بن المغيرة القيسي مولاهم; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
‘Abd Allaah bin Masud reported the Apostle of Allaah(ﷺ) as saying “Listening and Obedience are binding on a Muslim whether he likes or dislikes, so long as he is not commanded for disobedience (to Allaah). If he is commanded to disobedience (to Allaah), no listening and disobedience are binding (on him).
Grade: Sahih

Hadith #2731 - Sunan Abi Dawud - Aisha bint Abi Bakr; Fdyl bin Sulaiman al-Nmyry فضيل بن سليمان النميري; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Urwa ibn al-Zubayr عروة بن الزبير; Yahya bin Ma'in يحيى بن معين; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
I supplied water to my companions on the day of Badr.
Grade: Sahih

Hadith #2795 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Hafs bin Ghyath حفص بن غياث; Ja'far bin Rabi'ya bin Shrhbyl جعفر بن ربيعة بن شرحبيل; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
The Prophet (ﷺ) sacrificed two horned rams which were white with black markings and had been castrated. When he made them face the qiblah, he said: I have turned my face towards Him. Who created the heavens and the earth, following Abraham’s religion, the true in faith, and I am not one of the polytheists. My prayer, and my service of sacrifice, my life and my death are all for Allah, the Lord of the Universe, Who has no partner. That is what I was commanded to do, and I am one of the Muslim
Grade: Da'if

Hadith #2860 - Sunan Abi Dawud - Abu Tha'laba al-Khushni; Hmad bin Khalid al-Khyat حماد بن خالد الخياط القرشي; Mu'awiya bin Salah bin Hadayr معاوية بن صالح بن حدير; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
The Prophet (ﷺ) said: He said: He who sticks to a king is perverted. This version adds: The nearer a servant (of Allah) goes to a king, the farther he keeps away from Allah.
Grade: Da'if

Hadith #3087 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Ibn Ishaq محمد بن إسحاق بن يسار‎; Isma'il bin Umayya bin 'Amr إسماعيل بن أمية بن عمرو; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Wahb bin Jarir bin Hazim bin Zayd وهب بن جرير بن حازم بن زيد; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
Al-Miqdad went to Baqi’ al-Khabkhabah for a certain need. He found a mouse taking out a dinar from a hole. It then continued to take out dinars one by one until it took out seventeen dinars. It then took out a red purse containing a dinar. There were thus eighteen dinars. He took them to the Prophet (ﷺ), informed him and said to him: Take its sadaqah. The Prophet (ﷺ) asked him: Did you extend your hand toward the hole? He replied: No. The Messenger of Allah (ﷺ) then said: May Allah bless
Grade: Da'if

Hadith #3301 - Sunan Abi Dawud - Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج; Tawus bin Kaysan طاوس; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) saw a man that he was supported between his sons. He asked about him, and (the people) said: He has taken a vow to walk (on foot). Thereupon he said: Allah has no need that this man should punish himself, and he ordered him to ride. Abu Dawud said: ‘Amr b. Abi ‘Amir has also narrated a similar tradition from al-A’raj on the authority of Abu Hurairah from the Prophet (ﷺ).
Grade: Sahih

Hadith #3337 - Sunan Abi Dawud - Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
Abu Safwan said: I came to the Messenger of Allah (ﷺ) at Mecca before his immigration. He then narrated the rest of the tradition, but he did not mention the words “who was weighing for payment”. Abu Dawud sad: Qais also transmitted it as Sufyan said: The version of Sufyan is authoritative.
Grade: Sahih

Hadith #3373 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Jabir ibn 'Abdullah; Sufyan bin 'Uyaynah سفيان بن عيينة; Sulaiman bin Atyq سليمان بن عتيق; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
The Prophet (ﷺ) forbade the sale of fruits till they were clearly in good condition , and (ordered that) they should not be sold but for dinar or dirham except Araya.
Grade: Sahih

Hadith #3405 - Sunan Abi Dawud - Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade muzabanah, muhaqalah and thunya except it is known.
Grade: Sahih

Hadith #3412 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج; Urwa ibn al-Zubayr عروة بن الزبير; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
When the Prophet (ﷺ) conquered Khaibar. He then narrated it like the tradition of Zaid (b. Abu al-Zarqa’). This version has: He then assessed the produce of the palm-trees and said: I take the job of picking the fruit myself, and I shall give you half of (the amount) I said.
Grade: Hasan

Hadith #3459 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hafs bin Ghyath حفص بن غياث; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Both parties in a business transaction have a right of option (to annul it) so long as they are not separated ; and if they tell the truth and make everything clear, they will be blessed in their transaction, but it they conceal anything and lie, the blessing on their transaction will be blotted out. Abu Dawud said: A similar tradition has also been transmitted by Sa’id b. Abi ‘Arubah and Hammad. As regards with Hammam, he said in his version: Until th
Grade: Sahih

Hadith #4997 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; al-Nu'man bin Bashir ibn Sa'd; al-Yzar bin Hryth al-Bdy al-Kwfy العيزار بن حريث; Hajjaj bin Muhammad al-Musaysi حجاج بن محمد المصيصي الأعور; Yahya bin Ma'in يحيى بن معين; Yonus bin Abi Ishaq يونس بن أبي إسحاق (Sunan Abi Dawud)
Messenger of Allah! I have a fellow-wife; will it be wrong for me to boast of receiving from my husband what he does not give me? He replied: the one who boasts of receiving what he has not been given is like him who has put on two garments of falsehood.
Grade: Sahih